Mobilization and utilization of energy substrates of Arca zebra (Bivalvia: Arcidae) in regards to the environment - Villarroel-Moreno, José A. (2016)
The analysis of biochemical components in marine species for human consumption is of great importance because it allows knowing the nutritional and energy properties of the organism. The biochemical profile of Arca zebra tissues was evaluated in this research in relation to environmental factors, with the purpose of using this information as an indicator of the reproductive dynamics and fattening periods of this important fishery resource. A total of 20 organisms were analyzed per month between July 2010 and July 2011. Total length (TL) was determined in each organism, and tissues were separated using spectrophotometry, leaving them at a constant weight for biochemical analyzes. TL differences were established monthly, with an annual average of 69.61 mm, staying above commercial size. Differences were detected for carbohydrates and proteins between months, with maximum values in March and July 2011, being the muscle the part with the highest content of both energy substrates, related to high levels of chlorophyll a. An inverse relationship was observed between carbohydrates and proteins in the three tissues in regards to the gonadal mass, suggesting a possible transfer during the reproductive process of A. zebra. The greatest lipid content without monthly variation was recorded in gonads due to the species reproductive synchrony. A. zebra shows its best nutritional condition during the periods from September to December and March to June. Commercialization and consumption is recommended during those months.